2020
DOI: 10.1177/0142331220934948
|View full text |Cite
|
Sign up to set email alerts
|

Linear active disturbance rejection control for hysteresis compensation based on backpropagation neural networks adaptive control

Abstract: This paper proposes a compound control framework for non-affine nonlinear systems facing hysteresis disturbance. The controller consists of linear active disturbance rejection control (LADRC) and backpropagation (BP) neural networks adaptive control. BP neural networks are utilized to arbitrarily approximate the uncertainty nonlinear caused by the deviation of control parameter from its nominal value and LADRC is designed to real-time estimate and compensate the disturbance with vast matched and mismatched unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…All uncertainties of the system are regarded as the total disturbance (Liu et al, 2021), which is defined as…”
Section: Control Scheme Designmentioning
confidence: 99%
“…All uncertainties of the system are regarded as the total disturbance (Liu et al, 2021), which is defined as…”
Section: Control Scheme Designmentioning
confidence: 99%
“…Many research studies have demonstrated NNs approximation capability (Nassajian and Balochian, 2021), and parallel structure, learning capability, approximation of nonlinear functions, and fault tolerance cause NNs to be considered in identification and control applications. The backpropagation algorithm revolutionized the use of NNs in the 1980s and led to the development of neural controllers (Liu et al, 2020). In the field of NNs, several creative ideas and advances have been developed, but the study of stability, robustness, and convergence of the closed-loop system are essential issues concerning the neural controllers.…”
Section: Introductionmentioning
confidence: 99%
“…It often limits the system performance-for example, by giving rise to undesirable inaccuracies or oscillations-and can even lead to instability [2][3][4][5]. In addition to hysteresis, disturbances widely exist in industrial systems and can degrade control performance and system stability [6,7].…”
Section: Introductionmentioning
confidence: 99%